Analysis Distribution Patterns and Correlation of Ecological Characteristics Affecting the Existence of the Maleo Birds (Macrocephalon maleo) in Central Sulawesi, Indonesia: Distribution and Ecological Drivers of Maleo in Central Sulawesi - Abd. Karim , Wahyudin; Hadisusanto, Suwarno; Wibawaning Astuti, Raden Roro Upiek Ngesti; Pudyatmoko, Satyawan (Journal of Tropical Life Science, 2026)
Macrocephalon maleo is an endemic bird species of Sulawesi that selects nesting sites based on specific environmental conditions, particularly optimal soil temperature, moisture, water content, soil weight, and texture (including clay, dust, and sand composition). However, studies examining the relationship between soil physical characteristics and microclimatic factors across multiple nesting sites remain limited. This study aims to analyze the distribution patterns and the correlation of ecological characteristics that influence the existence of maleo in Central Sulawesi. The research was conducted from February 2024 to March 2025 at seven locations with a total of 23 coordinate points, including nesting grounds near geothermal sources (Saluki, Lore Lindu National Park), coastal areas (Taima, Moilong, Batui, Ampana, and Balingara), and a riverbank area (Bukit Jaya). Field observations were carried out for 10 days at each location, during which 197 maleo birds were recorded. Maleo distribution patterns were analyzed using the Morisita Index, while the relationships between ecological factors and maleo presence were assessed using Pearson correlation analysis. The Morisita Index indicates a clumped distribution pattern, with values ranging from 2.0 to 5.0. The average sand temperatures recorded were 33.9°C in the geothermal area (Saluki TNLL); 35.0°C, 34.4°C, 35.4°C, 33.13°C, and 32.9°C in the coastal areas (Taima, Moilong, Batui, Ampana, and Balingara), and 36.1°C in the riverbank area (Bukit Jaya). The results indicate that soil-related ecological factors, particularly water content, soil texture, and sand weight, had a stronger influence on maleo presence than ambient microclimatic variables such as air temperature, humidity, wind speed, and light intensity. Soil texture influences water retention, aeration, heat absorption, and soil consistency. Sandy soils tend to absorb and release heat efficiently, thereby creating suitable incubation conditions for maleo eggs in natural nesting habitats.